Development And Validation Of Online Preconcentration Capillary Electrophoresis Methods For The Determination Of Selected Pharmaceutical Compounds In Aqueous Matrices - Semail, Nadhiratul-Farihin (2022)
In this study, several preconcentration strategies in capillary electrophoresis (CE) were developed to improve the sensitivity of detection of pharmaceutical compound in real aqueous matrices. This is due to the core challenge to develop simple and sensitive analytical method for trace analysis study of selected analytes (anticancer, antibiotic and non-steroidal anti-inflammatory drugs) are very limited. Higher interference level from complex matrix (biological, food and water) with analytical instrument poor detection capability directed to development of online preconcentration technique. The first technique termed sequential injection mode stacking was developed for the separation and determination of anticancer agent 5-fluorouracil (5-FU) and its metabolite namely, 5-fluoro-2-deoxyuridine (5-FdUrd) in human plasma obtained from cancer patients. In this technique, large sample volume was introduced through electrokinetic injection followed by hydrodynamic injection. Under the optimized experimental conditions, 614- and 643- fold and 782- and 803- fold sensitivity improvement was obtained for both 5-FU and its metabolite when compared with normal hydrodynamic and electrokinetic injection alone, respectively.